2004
DOI: 10.1002/clc.4960271111
|View full text |Cite
|
Sign up to set email alerts
|

Hemodynamic significance of heart rate in neurally mediated syncope

Abstract: SummaryBackground: Vasovagal and vasodepressor syncope are used interchangeably in the literature to describe the common faint syndrome, now collectively named neurally mediated syncope. The significance of heart rate (HR) in these reflex-induced reactions remains unclear.Hypothesis: The study was undertaken to investigate the hemodynamic significance of HR in tilt-induced neurally mediated syncope.Methods: In all, 113 patients with syncope of unknown etiology were studied by head-up tilt test with invasive he… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 35 publications
0
2
0
Order By: Relevance
“…In VVS patients, the catecholamine content in the blood increases in the supine position, especially the adrenaline content (18,22,23). Chosy et al (22) also found that the level of catecholamine in urine was higher in patients with syncope, and Chan et al (23) found that the average resistance of the circulation was mainly controlled by the sympathetic nervous system. The content of noradrenaline and adrenaline in the serum of VVS patients has also been reported to be slightly higher than people without VVS in the supine position.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In VVS patients, the catecholamine content in the blood increases in the supine position, especially the adrenaline content (18,22,23). Chosy et al (22) also found that the level of catecholamine in urine was higher in patients with syncope, and Chan et al (23) found that the average resistance of the circulation was mainly controlled by the sympathetic nervous system. The content of noradrenaline and adrenaline in the serum of VVS patients has also been reported to be slightly higher than people without VVS in the supine position.…”
Section: Discussionmentioning
confidence: 99%
“…min/L, t = 3.861, p < 0.01). In VVS patients, the catecholamine content in the blood increases in the supine position, especially the adrenaline content . Chosy et al.…”
Section: Discussionmentioning
confidence: 99%